2015
DOI: 10.1177/1535370215573396
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol synergistically augments anti-tumor effect of 5-FU in vitro and in vivo by increasing S-phase arrest and tumor apoptosis

Abstract: Many studies have shown that natural dietary agents, in combination with chemical agents, can improve the therapeutic response of cancers to chemotherapy and reduce the associated side-effects. In the present study, we investigated the therapeutic potential and mechanisms of anticancer effects for the combination of 5-fluorouracil (5-FU) and resveratrol (Res). In these studies, we employed the cancer cell lines TE-1 and A431 and an animal model of skin cancer. The presented results provide the first evidence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 35 publications
3
21
0
Order By: Relevance
“…43 Consistently, we found that ECA-109 and TE-1 cells are more resistant to 5-Fu than other chemosensitive esophageal cancer cells such as OE19 and OE33 cells (Fig. S3A) [44][45][46] and that 5-Fu induces prosurvival autophagy, and caspase-independent and autophagy-associated cell death (Fig. 5D and 6C).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…43 Consistently, we found that ECA-109 and TE-1 cells are more resistant to 5-Fu than other chemosensitive esophageal cancer cells such as OE19 and OE33 cells (Fig. S3A) [44][45][46] and that 5-Fu induces prosurvival autophagy, and caspase-independent and autophagy-associated cell death (Fig. 5D and 6C).…”
Section: Discussionsupporting
confidence: 75%
“…S3A), which was consistent with previous reports. 44,45 Unexpectedly, these cells were more 5-Fu-resistant than other chemosensitive cells such as OE19 (IC 50 = 3.03 μg/ml) and OE33 (IC 50 = 1.24 μg/ml), 46 implying that ECA-109 and TE-1 cells were 5-Fu-resistant. A recent study showed that 5-Fu-induced cell death in chemoresistant esophageal cancer cells is apoptosis-independent, and that autophagy exerts a protective effect.…”
Section: -Fluorouracil Induces Protective Autophagy In Esophageal Camentioning
confidence: 94%
“…The agent was shown to induce apoptosis in such cancer cells as skin cancer cells, 35) colon cancer cells, 36) and neuroblastoma Cells, 37) whereas was indicated to exert the protective role against apoptosis in the human tenocytes, 38) in endothelial cells 39) and in other types of cells, 40) particularly, under the pressure of oxidative stress. [40][41][42] And in this study, we confirmed the protective role of RSV and the Sirt 1 activation against the H 2 O 2 -induced apoptosis in MC3T3-E1 osteoblast cells.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings consistent with Priyadarsini et al (2010) that 5-FU works by causing the G1/S arrest and induces apoptosis by inhibiting the biosynthesis process. MMDP containing quercetin suppresses the viability of HeLa cells in G2/M phase and induces apoptosis through mitochondrial pathways (Priyadarsini et al, 2010;Dun et al, 2015). The presence of p21 interferes with CDK-cyclin interactions, thereby, inhibiting progression of the cell cycle (Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%